NOTCH1 Activation Negatively Impacts on Chronic Lymphocytic Leukemia Outcome and Is Not Correlated to the NOTCH1 and IGHV Mutational Status - Baldoni, Stefano; Del Papa, Beatrice; De Falco, Filomena; Dorillo, Erica; Sorrentino, Carlo; Rompietti, Chiara; Adamo, Francesco Maria; Nogarotto, Manuel; Cecchini, Debora; Mondani, Elena; Silva Barcelos, Estevao Carlos; Moretti, Lorenzo; et al. (Frontiers in Oncology, 2021)
NOTCH1 mutations and deregulated signal have been commonly found in chronic lymphocytic leukemia (CLL) patients. Whereas the impact of NOTCH1 mutations on clinical course of CLL has been widely studied, the prognostic role of NOTCH1 activation in CLL remains to be defined. Here, we analyzed the activation of NOTCH1/NOTCH2 (ICN1/ICN2) and the expression of Jagged 1 (JAG1) in 163 CLL patients and evaluated their impact on TTFT (Time To First Treatment) and OS (Overall Survival). NOTCH1 activation (ICN1+) was found in 120/163 (73.6%) patients. Among them, 63 (52.5%) were NOTCH1 mutated (ICN1+/mutated) and 57 (47.5%) were NOTCH1 wild type (ICN1+/WT). ICN1+ patients had a significant reduction of TTFT compared to ICN1-negative (ICN1-). In the absence of NOTCH1 mutations, we found that the ICN1+/WT group had a significantly reduced TTFT compared to ICN1- patients. The analysis of IGHV mutational status showed that the distribution of the mutated/unmutated IGHV pattern was similar in ICN1+/WT and ICN1- patients. Additionally, TTFT was significantly reduced in ICN1+/ICN2+ and ICN1+/JAG1+ patients compared to ICN1-/ICN2- and ICN1-/JAG1- groups. Our data revealed for the first time that NOTCH1 activation is a negative prognosticator in CLL and is not correlated to NOTCH1 and IGHV mutational status. Activation of NOTCH2 and JAGGED1 expression might also influence clinical outcomes in this group, indicating the need for further dedicated studies. The evaluation of different NOTCH network components might represent a new approach to refine CLL risk stratification.